Covid-19 crisis management in Mexico: initial reopening / Covid-19 gestão de crise no México: reabertura inicial - Bahena, Benjamin Mendez; Moreno, Jorge Culebro; Hernandez, Pablo Cruz (Revista de Direito da Cidade, 2021)
Abstract The COVID-19 pandemic has shaken the whole world throughout 2020. In Mexico, the management of this crisis has fallen upon a federal administration that took power in December 2018 and promised to prioritize the poor and the marginalized. On the other hand, the health care system has been neglected for many years and is undergoing a transformation process (OECD, 2019; Presidency of the Republic, 2019). The present paper examines how federal government organizations managed the initial phase of the crisis, involving general confinement at the national level, and the first six weeks of the gradual reopening of activities, the so-called "new normality," which has been implemented by subnational governments. We employ crisis management theory as a theoretical framework to analyze coordination instruments in a profoundly fragmented health system, leadership styles, and the implementation of voluntary quarantine avoiding coercive measures. Concerning our methodology, we describe a mixed case study based on federal regulatory instruments, abundant publicly-available official information, and a press review for the study period. Finally in the concluding section, we point out the reasons why we consider that the management of the crisis in Mexico has been acceptable during the first months of the crisis. Keywords: crisis management, coordination, Mexico, COVID-19, reopening Resumo A pandemia COVID-19 abalou o mundo inteiro ao longo de 2020. No México, a gestão desta crise recaiu sobre um governo federal que assumiu o poder em dezembro de 2018 e prometeu priorizar os pobres e os marginalizados. Por outro lado, o sistema de saúde foi negligenciado por muitos anos e passa por um processo de transformação (OCDE, 2019; Presidência da República, 2019). O presente trabalho examina como os órgãos do governo federal administraram a fase inicial da crise, envolvendo o confinamento geral em nível nacional, e as primeiras seis semanas de reabertura gradativa das atividades, a chamada "nova normalidade", que vem sendo implementada por governos subnacionais. Empregamos a teoria da gestão de crises como referencial teórico para analisar instrumentos de coordenação em um sistema de saúde profundamente fragmentado, estilos de liderança e a implementação de quarentena voluntária evitando medidas coercitivas. Com relação à nossa metodologia, descrevemos um estudo de caso misto com base em instrumentos regulatórios federais, abundantes informações oficiais disponíveis ao público e uma revisão da imprensa para o período de estudo. Finalmente, na seção final, destacamos as razões pelas quais consideramos que a gestão da crise no México foi aceitável durante os primeiros meses da crise. Palavras-chave: gestão de crise, coordenação, México, COVID-19, reabertura